2019
DOI: 10.3892/mco.2019.1853
|View full text |Cite
|
Sign up to set email alerts
|

Global serum metabolomics profiling of colorectal cancer (Review)

Abstract: Accurate diagnosis of colorectal cancer (CRC) relies on the use of invasive tools such as colonoscopy and sigmoidoscopy. Non-invasive tools are less sensitive in detecting the disease, particularly in the early stage. A number of researchers have used metabolomics analyses on serum/plasma samples of patients with CRC compared with normal healthy individuals in an effort to identify biomarkers for CRC. The aim of the present review is to compare reported serum metabolomics profiles of CRC and to identify common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…Amino acids have been reported to be associated with other types of cancer in earlier reviews [ 88 , 89 , 90 , 91 ]. The amino acids identified in our meta-analyses (methionine, tryptophan and proline) were identified in previous reviews, although the direction of association is different for proline (i.e., positive association in our meta-analysis on lung cancer but inverse association for other cancer types) [ 88 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids have been reported to be associated with other types of cancer in earlier reviews [ 88 , 89 , 90 , 91 ]. The amino acids identified in our meta-analyses (methionine, tryptophan and proline) were identified in previous reviews, although the direction of association is different for proline (i.e., positive association in our meta-analysis on lung cancer but inverse association for other cancer types) [ 88 , 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past several years, a number of global metabolomic studies on CRC have been published. These studies utilized diverse biological specimens, including blood (plasma/serum) as the most common type [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], followed by tissue [ 27 , 39 , 40 , 41 , 42 ], feces [ 39 , 40 , 43 ], and urine [ 44 , 45 ], while others aimed specifically to detect volatile metabolites in breath and in other types of biospecimens [ 21 , 46 ]. To our knowledge, only two of these were prospective studies where biospecimens were collected before cancer development [ 26 , 34 ], aiming to identify etiological pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Blood is the most widely used clinical specimens. Hashim et al [ 23 ] recently reviewed the results of blood-based global metabolomic studies for CRC. The authors identified nine studies and found that the number of annotated metabolites in each study vastly varied from 14 [ 25 ] to 447 [ 34 ], not necessarily in a platform-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations